Population size and breeding success of Icelandic Whooper Swans Cygnus cygnus: results of the 2010 international census - Hall, Colette; Glanville, Jacqueline; Boland, Helen; Einarsson, Ólafur; McElwaine, Graham; Holt, Chas A; Spray, Christopher J; Rees, Eileen C (Wildfowl, 2012)
Trends in total population size and mid-winter distribution have been determined for the Icelandic Whooper Swan population through coordinated international censuses, undertaken in January across its wintering range in Britain, Ireland and Iceland, at c. 5-yearly intervals from 1986 onwards. A total of 29,232 swans recorded during the sixth international census in January 2010 represented an increase of 11% on the previous census in 2005 and is the highest census total to date. Overall, 35.8% of the population (10,452 swans) was recorded in the Republic of Ireland, 30.8% (8,999) in England, 15.8% (4,616) in Northern Ireland, 9.1% (2,659) in Scotland and 7.8% (2,278) in Iceland, with the combined total in Wales and the Isle of Man accounting for < 1% of birds counted. There was a significant increase across censuses (1986–2010) in the proportion of birds wintering in England, in comparison with the rest of the range, whereas the Republic of Ireland and Scotland saw a significant decline. This suggests an overall shift to the southeast in the swans’ winter distribution, though a prolonged period of cold, snowy weather prior to the January 2010 census may have resulted in more birds moving south from Scotland, or potentially from mainland Europe, in this year. The majority of Whooper Swans in Ireland were recorded on pasture in 2010, whilst in Britain they were seen mainly on arable land. Although the frozen conditions in 2010 are likely to have influenced habitat choice, there has been a general increase in the use of arable land by Whooper Swans since 1995.